Media Puzzle Picture dalam Keterampilan Berbicara Bahasa Jerman - Usman, Misnawaty; Garim, Idawati; Ernawati, Ernawati (Universitas Negeri Makassar, 2024)
Abstract. The Effectiveness of Puzzle Picture Media in German Speaking Skills (Sprechfertigkeit) ofstudents at German Language Education Study Program, Faculty of Language and Literature, Makassar State University. This research was conducted to obtain data and information regarding students' German speaking skills using Puzzle Picture Media. This research is a Quasi-Experimental research where data is collected through speaking skills tests. Data were analyzed using t-test. The population of this study were students from the German Language Education Study Program, Faculty of Language and Literature, Makassar State University, consists of two classes with 57 students. The sample used was a random sampling consists of 57 students, namely 29 class A students as the experimental class and 28 class B students as the control class. The results of data analysis obtained t count 8.83 > t table 2.004 at alpha level of 0.05. The results of the research show that the Puzzle Picture media is effective in speaking skills of students at German Language Education Study Program, Faculty of Language and Literature, Makassar State UniversityKeyword: Media, Puzzle Picture, Speaking Skills